aerial - Baumgartner, Mark F.; Bonnell, Julianne; Van Parijs, Sofie M.; Corkeron, Peter J.; Hotchkin, Cara; Ball, Keenan; Pelletier, Léo-Paul; Partan, Jim; Peters, Don; Kemp, John; Pietro, Jeff; Newhall, Kris; et al. (Dryad Digital Repository, 2019)
Aerial survey results for flights conducted by the New England Aquarium (NEAq) and NOAA Northeast Fisheries Science Center